Manipulation of the growth and body composition of mealworms, Tenebrio molitor - Hill, Victoria (2024)
Insects have received increased attention as a potential sustainable source of dietary or feed protein to partially replace feed for livestock. The aim of this thesis was to investigate the potential for manipulation of Tenebrio molitor larvae (mealworm) body composition, ideally increasing the proportion of protein and decreasing fat body composition.